Black is a country : race and the unfinished struggle for democracy - Singh, Nikhil Pal (ACLS Humanities E-Book., 2005)
"Nikhil Pal Singh asks what happened, to the wordly and radical visions of equality that animated black intellectual activists from W.E.B. Du Bois in the 1930s to Martin Luther King, Jr., in the 1960s. In so doing, he constructs an alternative history of civil rights in the twentieth century, a long civil rights era, in which radical hopes and global dreams are recognized as central to the history of black struggle." "Finding racism embedded within the universalizing tones of reform-minded liberalism at home and global democratic imperatives abroad, race radicals alienated many who viewed them as dangerous and divisive. Few wanted to hear their message then, or even now; and yet, as Singh argues, their passionate skepticism about the political promises made on behalf of the U.S. liberal democracy remains as indispensable to the project of racial justice today as it ever was."--Jacket.